Human Umbilical Cord Wharton Jelly-Derived Adult Mesenchymal Stem Cells, in Biohybrid Scaffolds, for Experimental Skin Regeneration - Pia Montanucci; Camilla di Pasquali; Ivana Ferri; Teresa Pescara; Ilaria Pennoni; Paola Siccu; Angelo Sidoni; Valerio Cervelli; Giuseppe Basta; Riccardo Calafiore (Hindawi Limited, 2017)
The ultimate goal for skin tissue engineering is to regenerate skin lesions to allow the full restoration of morphological and functional properties as what they were before injury. To this end, we have assembled a new prototype of a biomimetic human umbilical cord adult mesenchymal stem cell (hUCMS)/fibrin-based scaffold. We have fully characterized the proposed dermal equivalent (DE) in vitro, to assess morphological, functional, and biological properties of the encased cells. We transplanted DE subcutaneously into immunocompetent rodents, to verify its full biocompatibility. Finally, we studied DE graft effects on full-thickness wounds, in immunocompetent mice to demonstrate its capability to drive the healing process in the absence of significant scarring tissue. The excellent outcome of these in vivo studies fuels hope that this new approach, based on a biohybrid DE, may be applied to the operative treatment of skin lesions (i.e., diabetic foot ulcers and burns) in man.